Evaluating the potential of kit-based 68Ga-ubiquicidin formulation in diagnosis of infection: a pilot study68Ga. Issue 3 (March 2019) - Bhusari, Priya; Bhatt, Jyotsna; Sood, Apurva; Kaur, Ruchikapreet; Vatsa, Rakhee; Rastogi, Ashu; Mukherjee, Archana; Dash, Ashutosh; Mittal, Bhagwant Rai; Shukla, Jaya
Abstract : Objective: The aim was to evaluate the diagnostic potential of 68 Ga-ubiquicidin positron-emission tomography/computed tomography (PET/CT) in imaging patients with infection. Materials and methods: 68 Ga-NOTA-ubiquicidin ( 68 Ga-UBI) was prepared by addition of freshly eluted 68 Ga-chloride from 68 Ge/ 68 Ga generator into the NOTA-ubiquicidin vial and incubated at room for 15 min at 90°C. After compounding of the radiopharmaceutical, quality control using instant thin-layer chromatography, culture and endotoxin estimation was performed. Patients with suspected infection associated with diabetic foot, cellulitis and fracture were selected for the pilot study investigation to evaluate the ability of the tracer 68 Ga-UBI in localization at infection sites. The PET/CT findings were compared with other diagnosis like microbial culture reports and bone scintigraphy to evaluate true positives or negatives in the study. Results: The current study demonstrated the potential of kit-based 68 Ga-UBI in localization of infection sites in most of the patients proven positive for infection on culture tests and bone scintigraphy. The kit could offer radiolabeling yield more than 95% in 15 min incubation at 90°C. Quality control rendered the kit as a clinical grade preparation with endotoxin content less than 10 EU/ml and sterility up to 14 days of culture incubation. Eight of 10 patients underwent culture test and showed positive results. Two patients had undergone three-phase bone scan as an indirect sign of active infection. 68 Ga-UBI PET/CT showed tracer localization in four of eight culture-positive patients. Tracer localization was observed in one of two patients whose culture reports were not available. 68 Ga-UBI failed to identify infection in four patients with culture-positive results. Conclusion: The present study concluded that 68 Ga-UBI prepared using NOTA-UBI kit is a potential agent in targeting infections associated with disease conditions including diabetic foot, cellulitis and fracture. The patient selection holds significance in accurate diagnosis using 68 Ga-UBI PET/CT.